Business Model Development Strategy on Property Industry: Case Study on PT CNI - Mochammad. M. Ali, Trevy. A. Dinna, Mukhamad Najib, (Jurnal Manajemen, 2020)
PT CNI is a property developer company located in Cibubur. A high demand of residence leads many developer companies offer some types of housing in this area. PT CNI is currently experiencing a sales-declining, due to the high level of business competition and the sluggish national property market. Therefore, a new strategy formulation is needed that could be applied to re-increase company sales. This study aims to develop a company's strategy by describing and improving the business model of the company based on business model canvas (BMC), IE matrix, SWOT analysis, and blue ocean strategy approach. The data is collected by interviews, questionnaires, and literature studies. Informants were determined through a purposive sampling technique. From the results of the analysis, several strategies were formulated. Then the strategies were mapped back to the new BMC. The improvement shows that there are enhancements to some elements in the company's BMC.